Block LU decompositon of a band matrix on a systolic array - Robert, Yves (International journal of computer mathematics, 1985)
After a brief discussion on systolic arrays for band matrix LU or QR decomposition, we introduce a new systolic array for the block 2x2 LU decompositon of a band matrix A. This array is an hexagonally connected systolic array whose efficiency is e = ½ although its hardware requirement is the same as the LU decomposition array of Kung and Leiserson [8]. In the last section we consider the systolic solution of linear systems of matrix A:: we show that computing the block LU decomposition of A is twice more efficient than computing the usual LU decomposition of A.